PEMANFAATAN BAHAN AJAR VIDEO DALAM PEMBELAJARAN MATEMATIKA DI MI DARUSSA’ADAH TULUNGAGUNG - Wahyu Purwandari (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This research aims to investigate the utilization of video teaching materials in mathematics education at MI Darussa’adah Tulungagung in more detail. A case study design is used in conjunction with a qualitative approach as the research methodology. In this study, documentation studies, observations, and interviews were used as data gathering methods. The results show that the use of video instructional resources in grade V mathematics instruction at MI Darussa'adah Tulungagung is highly successful. By using these video teaching resources, educators may improve their students' comprehension of the topic and increase their enthusiasm to study, which makes mathematics instruction more dynamic and engaging.